The community forests of Mexico : managing for sustainable landscapes - Bray, David Barton; Merino-Perez, Leticia; Barry, Deborah (University of Texas Press, 2005)
Mexico leads the world in community management of forests for the commercial production of timber. Yet this success story is not widely known, even in Mexico, despite the fact that communities around the globe are increasingly involved in managing their own forest resources. To assess the achievements and shortcomings of Mexico's community forest management programs and to offer approaches that can be applied in other parts of the world, this book collects fourteen articles that explore community forest management from historical, policy, economic, ecological, sociological, and political perspectives. The contributors to this book are established researchers in the field, as well as many of the important actors in Mexico's nongovernmental organization sector. Some articles are case studies of community forest management programs in the states of Michoacán, Oaxaca, Durango, Quintana Roo, and Guerrero. Others provide broader historical and contemporary overviews of various aspects of community forest management. As a whole, this volume clearly establishes that the community forest sector in Mexico is large, diverse, and has achieved unusual maturity in doing what communities in the rest of the world are only beginning to explore: how to balance community income with forest conservation. In this process, Mexican communities are also managing for sustainable landscapes and livelihoods.